The London Nobody Knows ; Les Bicyclettes de Belsize - Cohen, Norman; Hickox, Douglas; Maher, Terry; Suschitzky, Wolfgang; Huxtable, Judy; May, Anthony; Goddard, Leslie (Optimum, 2008)
The London Nobody Knows (1967): "The London Nobody Knows" is a tour of London, narrated by James Mason. Based on the book by Geoffrey Fletcher ('the great forgotten London writer'), it is a 45 minute snapshot of late 1960s London and is a fascinating time capsule of the remnants of a bygone age before the capital's extensive redevelopment in the late 1960s and 70s. [www.moviemail.com]